The influence of occupational stress on the professional performance - Rus, Mihaela; Sandu, Mihaela Luminita; Pelican (Maliu), Tania Madalina; Ciocanu, Mihai; Tabacaru (Ionescu), Alina (Technium Social Sciences Journal, 2022)
No field of activity is free of stress, but it is known from the multitude of studies conducted that certain sectors are affected by stress well above average. This phenomenon is closely related to the appearance of nervousness, anxiety, anger, panic, tension, fears, physical and mental fatigue that modern man goes through. Stressors are related to the personality structure, the type of emotional reactivity, the behavioral and attitudinal characteristics, but also to the cognitive style and intellectual abilities of each individual, to his perceptions related to work situations. Studies on the effects of occupational stress on nurses are quite a few, maybe due to the assumption that this job is by its nature, very stressful. The closure of health facilities in our country as a result of government policy, has led to an increase in aggressive behaviors among medical staff as a result of stressors caused by the new situation created. The research aims to investigate occupational stress by looking at changes in personality structure in adulthood. We considered it necessary to study the stress factors and their effects on the majority of nurses, as their activity is particularly important for the quality of life of patients, and this would not be achieved satisfactorily, under the influence of the harmful effects of stress. Not all the nurses in the same work environment will show low job satisfaction, but only those whose traits are weak and make them susceptible to organizational stressors. Precisely for this reason, the main hypothesis of this research starts from the fact that a greater control over the sources of pressure determines the reduction of professional stress in adults